Antioxidantal and histopathological effects of mirazid on gentamicin-induced renal damage in rats - AbdEl-Mongy, Mahmoud; Y. Nasr, Mohamed; H. Elsayed, Ibrahim; Soliman, Asmaa M. (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
The present study evaluates the biochemical effect of mirazid(MZ) in rats of GMtamicin(GM)-Â induced renal damage. Albino male rats (Rattus norvegicus), weighing 40â€“50 g were dividedÂ into 6 groups; normal saline, orally trated mirazid 10 mg/kg, GM 100mg/kg, intraperitoneallyÂ (i.p) for 10 days, MZ at 2.5, 5, and 10 mg/kg, per oral for 10 days with the same concentrationÂ of GM, MZ administered concurrently with GM for 10 days. We investigated the effects of MZÂ on GM-induced nephrotoxicity. GM treatment caused nephrotoxicity as evidenced by markedÂ elevation in serum Cr and blood urea (152.3 Â± 8.6 mg/dL, 1.6 Â± 0.12 mg/dL resp) whenÂ compared to the saline treated group. GM administration increased renal MDA and NOÂ GMeration but decreased SOD and CAT activities, and GSPx (glutathione peroxidase)Â compared to normal control. MZ administration with GM injections caused significantlyÂ decreased MDA, NO GMeration and increased SOD, CAT activities and GSPx activity whenÂ compared with GM alone. Histopathological analysis revealed epithelial loss with intense +granular deGMeration in GM treated rats, whereas MZ decrease the severity of GM-inducedÂ renal damage. To conclude, our data suggest that MZ exhibits some antioxidantal effect againstÂ GM nephrotoxicity, as it has a potent scavenger of free radicals to prevent the toxic effects ofÂ GM at both the biochemical and histological level and further studies on its mechanism ofÂ action and side effects are wanted.